Identification of a serotonin N-acetyltransferase from Staphylococcus pseudintermedius ED99 - Hafza, Nourhane; Li, Ningna; Luqman, Arif; Götz, Friedrich (Frontiers in Microbiology, 2023)
Serotonin N-acetyltransferase (SNAT) catalyzes the biosynthesis of N-acetylserotonin (NAS) and N-acetyltryptamine (NAT), two pleiotropic molecules with neurotransmitter functions. Here, we report the identification of a SNAT protein in the genus Staphylococcus. The SNAT gene identified in Staphylococcus pseudintermedius ED99, namely SPSE_0802, encodes a 140 residues-long cytoplasmic protein. The recombinant protein SPSE_0802 was expressed in E. coli BL21 and found to acetylate serotonin (SER) and tryptamine (TRY) as well as other trace amines in vitro. The production of the neuromodulators NAS and NAT was detected in the cultures of different members of the genus Staphylococcus and the role of SPSE_0802 in this production was confirmed in an ED99 SPSE_0802 deletion mutant. A search for SNAT homologues showed that the enzyme is widely distributed across the genus which correlated with the SNAT activity detected in 22 out of the 40 Staphylococcus strains tested. The N-acetylated products of SNAT are precursors for melatonin synthesis and are known to act as neurotransmitters and activate melatonin receptors, among others, inducing various responses in the human body. The identification of SNAT in staphylococci could contribute to a better understanding of the interaction between those human colonizers and the host peripheral nervous system.